Three‐dimensional multidetector computed tomography versus conventional 2‐dimensional transesophageal echocardiography for annular sizing in transcatheter aortic valve replacement: Influence on postprocedural paravalvular aortic regurgitation. Issue 6 (19th July 2013) - Hansson, Nicolaj C.; Thuesen, Leif; Hjortdal, Vibeke E.; Leipsic, Jonathon; Andersen, Henning R.; Poulsen, Steen H.; Webb, John G.; Christiansen, Evald H.; Rasmussen, Lars E.; Krusell, Lars R.; Terp, Kim; Klaaborg, Kaj E.; et al.
<x xml:space="preserve">Abstract</x> Objectives In transcatheter aortic valve replacement (TAVR), the influence of aortic annular assessment with either multidetector computed tomography (MDCT) or conventional transesophageal echocardiography (TEE) on the incidence of postprocedural paravalvular aortic regurgitation (PAR) was evaluated. Background PAR remains a major limitation in TAVR. Appropriate selection of transcatheter heart valve (THV) size is crucial to prevent PAR. Methods Outcomes following TAVR with a balloon‐expandable THV were compared in two retrospective cohorts identified according to whether THV size selection was based on TEE (study group 1, n = 80) or MDCT (study group 2, n = 58). Results The two study groups were comparable with regard to baseline clinical, risk score, and echocardiographic characteristics. The incidence of moderate/severe PAR was lower in study group 2 than in group 1, 8.6% versus 28.8% (P < 0.01). The difference between the THV nominal diameter and MDCT annular diameter was predictive of moderate/severe PAR (AUC 0.84; 95% CI: 0.72–0.92). Neither age, gender, body mass index, annular eccentricity index, aortic valve calcification nor the difference between the THV diameter and the TEE annular diameter predicted postprocedural PAR. Increased THV oversizing relative to the MDCT mean annular diameter was associated with reduced severity of PAR. No difference in perprocedural complications between two study groups was observed. Conclusion MDCT‐based annular sizing in TAVR significantly reduces postprocedural PAR, and THV oversizing appears pivotal in this aspect. Further delineation of the optimal degree of THV oversizing is needed. © 2013 Wiley Periodicals, Inc.